Older adults' perceptions of the risks associated with contemporary gambling environments: Implications for public health policy and practice - Pitt, Hannah; McCarthy, Simone; Thomas, Samantha L.; Randle, Melanie; Marko, Sarah; Cowlishaw, Sean; Kairouz, Sylvia; Daube, Mike (Frontiers in Sociology, 2023)
Rapid changes in the Australian gambling environment have amplified the risks for gamblers and pose significant threats to public health. Technological advances, saturation of marketing, and the embedding of gambling in sport have all contributed to significant changes in the gambling risk environment. Older adults have witnessed the changes to the way gambling is provided and promoted in public spaces, but little is known about how these changes have shaped the way they conceptualise the risks associated with gambling. Guided by critical qualitative inquiry, semi-structured interviews were conducted with 40 Australian adults aged 55 years and older, who had gambled at least once in the last 12 months. Reflexive thematic analysis was used to interpret the data. Participants discussed gambling environments in Australia and how they had changed through the proliferation of gambling products, environments, and opportunities; the risks posed through the embedding of gambling in community and media environments; the role of technology in gambling environments; and the role of marketing and promotions in the changing gambling environments. Participants recognised that these factors had contributed to gambling environments becoming increasingly risky over time. However, despite the perception of increased risk, many participants had engaged with new gambling technologies, products, and environments. This research supports the adoption of public health responses that include consideration of the environmental, commercial, and political factors that may contribute to risky gambling environments.